2016
DOI: 10.1128/cvi.00115-16
|View full text |Cite
|
Sign up to set email alerts
|

An HIV gp120-CD4 Immunogen Does Not Elicit Autoimmune Antibody Responses in Cynomolgus Macaques

Abstract: ؉ T cell staining, and temporal trends in T cell subset frequencies served to assess whether anti-CD4 autoantibody responses were elicited by vaccination. We find that immunization with multiple high doses of rhFLSC did not elicit detectable antibody titers despite robust responses to rhFLSC. In accordance with these findings, immunized animals had no changes in circulating CD4 ؉ T cell counts or evidence of autoantibody reactivity with cell surface CD4 on primary naive macaque T cells. Collectively, these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
2
6
0
Order By: Relevance
“…The total plasmablasts were also not affected by the mucosal vaccine (Supplemental Figure 3C). In the present study, no antibodies were detected against CD4, as shown in Supplemental Figure 2A, consistent with the observations that rhFLSC did not raise anti-CD4 autoantibodies in any previous macaque studies, including a formal immunotoxicological study published by Schwartz et al (18). Other components, e.g., MVA, did not contain any xeno antigens.…”
Section: C and D)supporting
confidence: 93%
“…The total plasmablasts were also not affected by the mucosal vaccine (Supplemental Figure 3C). In the present study, no antibodies were detected against CD4, as shown in Supplemental Figure 2A, consistent with the observations that rhFLSC did not raise anti-CD4 autoantibodies in any previous macaque studies, including a formal immunotoxicological study published by Schwartz et al (18). Other components, e.g., MVA, did not contain any xeno antigens.…”
Section: C and D)supporting
confidence: 93%
“…Such development raises the question of the potential immunogenicity of this class of compound, a point of concern that is subject of future studies. It is worth noting, however, that immunization with multiple high doses of a chimeric antigen comprising gp120 linked to CD4 sequences did not elicit detectable autoantibody reactivity with cell surface CD4, despite a robust response to the antigen 56 .…”
Section: Discussionmentioning
confidence: 94%
“…This latter relationship is in accordance with other nonhuman primate studies of HIV vaccine concepts linking protection with Fc-mediated effector functions (see for examples [30] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] . FLSC-vaccinated animals did not exhibit autoreactive anti-CD4 autoantibodies or other detectable alterations in circulating CD4 + T cells [47] . A recent study showed that rhFLSC could be used as a component of a vaccination regimen that afforded protection in macaques via trained immunity [48] .…”
Section: Introductionmentioning
confidence: 85%